2023
DOI: 10.3390/mi14071341
|View full text |Cite
|
Sign up to set email alerts
|

Through-Holes Design for Ideal LiNbO3 A1 Resonators

Abstract: This paper proposes a method to realize ideal lithium niobate (LiNbO3) A1 resonators. By introducing subwavelength through-holes between the interdigital transducer (IDT) electrodes on the LiNbO3 surface, all unfavorable spurious modes of the resonators can be suppressed completely. It is convenient and valid for various IDT electrode parameters and different LiNbO3 thicknesses. Also, this method does not require additional device fabrication steps. At the same time, these through-holes can greatly reduce the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…Remarkably, seminal work by Yang et al has demonstrated A1 mode resonators operating within the 5 GHz range, showcasing a K 2 e f f value of 29% [15], thereby highlighting their considerable potential in the sub-6 GHz domain. Nevertheless, a substantial challenge associated with A1 mode resonators is their vulnerability to spurious modes [16][17][18][19], which constitute a critical barrier to their extensive application. Consequently, the strategic goal of minimizing or eradicating these spurious modes becomes an essential consideration for the advancement of high-performance A1 mode resonators.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, seminal work by Yang et al has demonstrated A1 mode resonators operating within the 5 GHz range, showcasing a K 2 e f f value of 29% [15], thereby highlighting their considerable potential in the sub-6 GHz domain. Nevertheless, a substantial challenge associated with A1 mode resonators is their vulnerability to spurious modes [16][17][18][19], which constitute a critical barrier to their extensive application. Consequently, the strategic goal of minimizing or eradicating these spurious modes becomes an essential consideration for the advancement of high-performance A1 mode resonators.…”
Section: Introductionmentioning
confidence: 99%
“…In a nutshell, for their current study on spurious modes in A1 mode resonators, they essentially focused on high-order spurious modes or other lamb modes away from the resonance. However, little attention was paid to spurious modes that are known as transverse modes, which also require further study as they affect the performance of A1 devices [ 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%